White-silicone rubber and copolymer-in-oil blend for ultrasound soft tissue mimicking material - Grillo, Felipe; Cabrelli, Luciana; Ribeiro, Leticia; Herculano, Rondinelli [UNESP]; Borges, Felipe [UNESP]; Pavan, Theo; Carneiro, Antonio (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Phantoms are objects manufactured using a tissue mimicking material (TMM) and largely used to test protocols and mimic clinical environment for medical training. The TMM should reproduce at least one biological property to allow the association with clinical situation. The gel made by the copolymer styrene-ethylene/butylene-styrene (SEBS) in mineral oil previously reported by our group is a stable TMM to ultrasound applications. Blends of white-silicone rubber and SEBS are demonstrated to be miscible. In this study we evaluated acoustical, mechanical and chemical properties changes by white silicone rubber adding in a SEBS for tissue mimicking materials purpose to verify the miscibility of white-silicone rubber and SEBS.